Don't tell me, show me: Reactions from those with lived experience to the 2020 revised IASP definition of pain - Isabel Jordan; Rachel Martens; Kathryn A. Birnie (Wiley, 2021)
Abstract In 2020, the International Association for the Study of Pain (IASP) revised the definition of pain, providing an update to IASP's original definition in place since 1979. The origins of the field of pediatric pain, born in part in the 1980s from the advocacy of Jill Lawson, mother to Jeffrey Lawson who experienced gross inadequacies in pain care as a premature infant, emphasize the critical need to listen to and act with the voice of people living with pain and their families and caregivers. Furthermore, the field of pediatric pain emerged in the mid‐1980s marking this revised definition of pain as the first opportunity within which the experience and science of pain in childhood has been considered. This invited commentary offers two lived experience reactions to the revised IASP definition of pain, from the perspective of one's own experience with pain during childhood and as parents and family members. Together, they highlight that the value of a revised definition must be judged on its ability to directly benefit children experiencing pain and their families. Their skeptical hope reflects their lived experience backed by empirical evidence demonstrating continued inequities and inadequacies in preventing and managing pediatric pain. We must mobilize together to ensure change in culture, knowledge, and behavior. With the combined efforts of researchers, healthcare professionals, and policymakers, in partnership with diverse people with lived experience, we can ensure that more effective action is taken to rapidly improve pain for children and their families.